The Effect of Storage Temperature In Cooler Bag on Breast Milk Quality - Runjati; Irmastuti Lukitaning Alam; Daru Lestyanto (International Journal of Nursing and Health Services (IJNHS), 2021)
Breast milk is a quality baby food because it contains nutrients and immunity. The high percentage of working mothers who breastfeed (92.5%) is directly proportional to the number of babies who consume pumped breast milk. It is feared that the storage of breast milk at a specified temperature and time can reduce its quality, including immunoglobulin A (IgA) levels. Objective: The objective of this study was to prove the effect of storage temperature on the quality of breast milk (IgA). Methods: This study used a quasi-experimental design with a pre-post-test design with a control group design. The sampling technique used purposive sampling of 32 nursing mothers in the experimental group and 32 nursing mothers in the control group included in the inclusion criteria (divided into control and experimental groups). The bivariate analysis utilized paired until t-test followed by independent t-test. Results: There was a decrease in IgA levels in the cooler bag storage temperature (4-8 0C) for 6 hours with an average difference of -18.264 ng/ml (p-value 0.012). IgA levels also decreased at room temperature storage (26 0C) for 6 hours with an average difference of -373.209 ng/ml (p-value 0.000). Different tests in the two groups had an average difference in IgA levels of -354.945 ng/ml (p-value 0.000), which meant significant differences. Conclusion: Storage temperature at cooler bag temperature 4-8 0C is better than room temperature of 26 0C on breast milk quality (IgA level).